YOGA FOR REHABILITATION: AN INTEGRATED APPROACH TO PHYSICAL AND NEUROLOGICAL CONDITIONS - Mondal, Soma (Journal of Creativity in Art and Design, 2024)
Yoga, an ancient practice rooted in Indian philosophy, has evolved into a modern therapeutic modality to address various physical and neurological conditions. This study explores the efficacy of yoga as a rehabilitation tool, synthesizing evidence from many sources, including randomized controlled trials, observational studies, and meta-analyses. Physical conditions such as chronic pain, osteoarthritis, and musculoskeletal disorders often lead to reduced mobility and quality of life. Concurrently, neurological conditions such as stroke, multiple sclerosis, and Parkinson's disease present unique challenges that require comprehensive management. In the context of rehabilitation, yoga's integrated approach offers a blend of physical postures, breathing techniques, meditation, and ethical principles that can provide holistic healing. The study highlights the adaptability of yoga to individual needs, which allows for tailoring interventions to specific conditions and patient preferences. Evidence suggests that yoga can improve physical function, enhance psychological well-being, reduce symptoms of anxiety and depression, and promote overall patient satisfaction. Applying yoga in rehabilitation presents opportunities to support conventional and alternative medical treatments. By emphasizing a mind-body connection, yoga offers a non-invasive, cost-effective option that complements existing rehabilitation strategies. The study also recognizes the need for standardized protocols, rigorous research methodologies, and collaboration among healthcare professionals to unlock yoga's potential in rehabilitation fully. Future research is urged to address these gaps and contribute to developing evidence-based guidelines. Integrating yoga into rehabilitation protocols provides a promising avenue to enhance physical and neurological recovery. Its inherent flexibility, multifaceted approach, and potential synergies with existing therapeutic methods underline yoga's relevance in contemporary healthcare practices.